PENGARUH PERCEIVED RISK TERHADAP CUSTOMER LOYALTY MELALUI SWITCHING COST - Windy Kaligis (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2016)
The objective of this study is to examine and analyze the effect of perceived risk on customer loyalty through switching cost of PT Go Jek Indonesia customers. The samples being used in this study is 154 respondents. Data collection method that is used in this study is purposive sampling. Hypothesis testing is conducted using Structuctural Equation Model (SEM). The findings of this study are perceived risk has negative effect on customer loyalty, perceived risk has negative effect on switching cost, switching cost has positive effect on customer loyalty, and perceived risk has positive effect on customer loyalty through switching cost.